已知x=根号3+根号2,y=根号3-根号2求(x^3-xy^2)⼀(x^4y+2x^3y^2+x^2y^3)

2025-02-25 05:54:56
推荐回答(2个)
回答1:

原式=x(x+y)(x-y)/x^2y(x^2+2xy+y^2)
=(x+y)(x-y)/xy(x+y)^2
=(x-y)/xy(x+y)
=(✓3+✓2-✓3+✓2)/(✓3+✓2)(✓3-✓2)(✓3+✓2+✓3-✓2)
=2✓2/2✓3
=✓6/3

回答2:

X =√3 +√2 /√3 - √2时,y =√3 - √2 /√3 +√2
的xy = 1

的xy =(√3 +√2)/(√ 3 - √2) - (√3 - √2)/(√3 +√2)= [(√3 +√2)2 - (√3 - √2)2] /(3-2)= 4√ 6

X + Y ==(√3 +√2)/(√3 - √2)+(√3 - √2)/(√3 +√2)= [(√3 +√2) 2 +(√3 - √2)2] /(3-2)= 10

∴X ^ 3-XY ^ 2 / X ^ 4Y +2 X ^ 1411 ^ 2 + X ^ 2Y ^ 3 = X(X 2-Y 2)/ [X 2 Y(X 2 +2 XY + Y 2)]

=(X + Y)(XY)/ [XY(X + Y)2]

=(XY)/ [XY(X + Y)]

= 4√6 /(1 * 10)

= 2√6月5日
希望能帮到你,并希望学习和进步O(∩_∩)O